Neurohumoral Pathway in Heart Failure - Dyah Wulan Anggrahini (ACI (Acta Cardiologia Indonesiana), 2019)
Heart Failure is now considered as one of the leading cause for mortality and morbidity. It is affecting several organs and cause organ damages due to the myocardial failure to pump inadequate oxygenated blood to the body including metabolites, to end organs and peripheral tissues.  Heart failure results from multifactorial mechanism including neurohumoral activations including increased activity of the sympathetic nervous system, renin-angiotensin aldosteron system, vasopression and the atrial natriuretic peptide. This neurohumoral pathway has significant contribution to the development of myocardial dysfunction that lead to clinical manifestation of heart failure. Some of the markers in these pathways have now been considered as an independent predictors of prognosis in heart failure patient.